2006
DOI: 10.1111/j.1532-950x.2005.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Scintigraphy for Diagnosis of Equine Paranasal Sinus Disorders

Abstract: Focal areas of moderate or marked IRU may be observed with primary sinusitis. Careful 3-dimensional localization of the lesion, along with consideration of other clinical and diagnostic findings should be performed to prevent false-positive diagnoses of periapical infection in such instances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 19 publications
1
36
0
2
Order By: Relevance
“…Because of the anatomical differences between adult and foals, further studies are necessary to describe normal changes related to age in young horses. Scintigraphic examination could be useful and complementary to CT in association with a fusion imagine technique for investigation of sinus diseases particularly of dental origin (Barakzai et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the anatomical differences between adult and foals, further studies are necessary to describe normal changes related to age in young horses. Scintigraphic examination could be useful and complementary to CT in association with a fusion imagine technique for investigation of sinus diseases particularly of dental origin (Barakzai et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Apical infections are conclusively diagnosed by a combination of clinical signs, oral lesions (pulpar exposure and/or draining periodontal tract) and radiographic changes, such as periapical lysis, apical clubbing and sclerosis. Further imaging modalities such as scintigraphy or computed tomography are of use in some cases to confirm the diagnosis (Barakzai et al . 2006).…”
Section: Diagnosis Of Dental Disordersmentioning
confidence: 99%
“…Radiography has good specificity but poor sensitivity for detecting periapical infections (Weller et al . 2001; Barakzai et al . 2006), although recent studies evaluating computed radiography have shown this imaging technology to have improved sensitivity compared to conventional film radiography (Casey et al .…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Scintigraphy has excellent sensitivity (95%) and moderate specificity (86%) for apical infections (Weller et al . 2001; Barakzai et al . 2006).…”
Section: Diagnostic Imagingmentioning
confidence: 99%